Berth allocation and quay crane assignment in a container terminal for the trade-off between time-saving and energy-saving. Issue 3 (August 2016) - He, Junliang
Abstract: This paper addresses the problem of integrated berth allocation and quay crane (QC) assignment for the trade-off between time-saving and energy-saving. This problem is formulated as a mixed integer programming model (MIP), in order to minimize the total departure delay of all vessels and the total handling energy consumption of all vessels by QCs. Furthermore, an integrated simulation and optimization method is developed, where the simulation is designed for evaluation and optimization algorithm is designed for searching solution space. Finally, numerical experiments are conducted to verify the effectiveness of the proposed method.